Indoor Air Pollution of Outdoor Origin: Mitigation Using Portable Air Cleaners in Singapore Office Building - Zuraimi Sultan; Jiayu Li; Jovan Pantelic; Stefano Schiavon (Aerosol and Air Quality Research)
Abstract Landscape fires in Indonesia and traffic pollution have been receiving increasing attention as sources of particulate matter (PM) in Singapore. Although mitigation measures to reduce PM levels using portable air cleaners (PACs) have been used in residential buildings, its application for office buildings is unknown. Using PAC, we demonstrated their potential for indoor particles removal in an office building and presented a method to evaluate their performance and estimate number of units to be deployed. Modelled and in-situ measured PAC effectiveness using up to twelve units was evaluated in three office sizes (30, 80 and 1490 m3). Measured effectiveness using indoor concentrations and indoor/outdoor ratios was obtained in a randomised intervention experimental design involving 3 weeks per location. Indoor particle concentration reductions in the three offices were dependent on particle size and confounded by variations in indoor emissions and outdoor levels resulting in low correlation and higher RMSE between modelled and measured effectiveness. PAC effectiveness computed using I/O ratios for removing UFP, PM2.5 and PM10 ranged 24–43%, 23–53% and 7–37% respectively. PAC has a higher in-situ effectiveness in small compared to larger spaces and the effectiveness is logarithmically dependent on the number of units deployed. We validated the use of our model to determine PAC effectiveness in the offices using up to eleven PACs (RMSE between modelled and measured data ranging from 3.9 to 6.6%). Lastly, we developed a design method to size the number of PAC needed for office buildings. The results from this study can be used for standards organization, policy makers and researchers interested in particle exposure reductions in large spaces.